The positive effects and underlying mechanisms of Undaria pinnatifida polysaccharides on type 2 diabetes mellitus in rats. Issue 23 (5th November 2021) - Li, Zhao-Rong; Jia, Rui-Bo; Luo, Donghui; Lin, Lianzhu; Zheng, Qianwen; Zhao, Mouming
Abstract : The aim of the current work was to investigate the anti-diabetic effects and underlying mechanisms of Undaria pinnatifida polysaccharides (UPP) based on a type 2 diabetes (T2DM) rat model. Abstract : The aim of the current work was to investigate the anti-diabetic effects and underlying mechanisms of Undaria pinnatifida polysaccharides (UPP) based on a type 2 diabetes (T2DM) rat model. The starch loading test showed that UPP administration could reduce blood glucose fluctuations caused by eating. Analysis of diabetic symptoms and biochemical profiles showed that UPP intervention markedly decreased fasting blood glucose level, mitigated insulin resistance, improved glucose tolerance, dyslipidemia and liver and kidney damage in diabetic rats. The 16S rRNA analysis demonstrated that UPP intervention could markedly change the intestinal microflora composition, causing increases in Alistipes, Bacteroides, Christensenellaceae _R-7_group, Desulfovibrio, Muribaculaceae _norank, Ruminococcaceae _UCG-013, and Ruminococcaceae _UCG-014, and a decrease in Escherichia-Shigella . Furthermore, RT-qPCR analysis results clarified that UPP administration distinctly activated the IRS/PI3K/AKT signaling pathway, restrained PEPCK, G-6-Pase and Egr-1 genes, and affected the relative expression of HMGCR and LDLR genes. This study demonstrates that UPP could be applied as an adjuvant agent for the management of T2DM.